2007
DOI: 10.1590/s0034-89102007000600006
|View full text |Cite
|
Sign up to set email alerts
|

Variáveis socioeconômicas e a transmissão de dengue

Abstract: The lack of an association between risk of occurrence of dengue and socioeconomic levels in almost all years studied indicates that this issue deserves further study, and may vary depending on the settings found in each municipality. It will be important to determine the spatial relationship between dengue transmission and other variables, such as degree of immunity in the population, effectiveness of control measures, degree of infestation by the vector; and population habits and behaviors, among others.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
24
0
23

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 21 publications
2
24
0
23
Order By: Relevance
“…Results similar to ours were found in the cities of Nova Iguaçu in the Baixada Fluminense, and in São José do Rio Preto, interior of São Paulo, where the highest incidence was observed in high or medium to high living status neighborhoods, contiguous to bad living status neighborhoods 19,20 .…”
Section: Discussionsupporting
confidence: 88%
“…Results similar to ours were found in the cities of Nova Iguaçu in the Baixada Fluminense, and in São José do Rio Preto, interior of São Paulo, where the highest incidence was observed in high or medium to high living status neighborhoods, contiguous to bad living status neighborhoods 19,20 .…”
Section: Discussionsupporting
confidence: 88%
“…Several variables have been used to identify the factors associated with dengue and, consequently, to provide a better basis for new proposals regarding the control of the disease. 14,15,24 The variable percentage of households connected with the general sanitary network explained the total variability of the average incidence rate of dengue in the municipality of Rio de Janeiro. The improvement in the sewage system has a great impact on the occurrence of infection and morbidity by many diseases.…”
Section: Discussionmentioning
confidence: 99%
“…For example, it did not include other possible variables related to the disease transmission, like water supply regularity, 18 the vector's spatial density, productivity of oviposition containers, building infestation rate. 9,15 Due to irregular water supply, the population stores water in recipients that may become oviposition containers of the mosquito. The diffi culty in accessing data on the vector limits its correlation with data on the disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some authors have not found any particular patterns associated with unfavorable socioeconomic conditions (9,33,36), while the work by Barcellos,et al (37) in Porto Alegre associated dengue cases with favorable socioeconomic conditions. The relationship of these variables to dengue may be due to unclear socioeconomic segmentation in the city and the location of sectors with better conditions near those with poor conditions (38,39).…”
Section: Discussionmentioning
confidence: 94%